Quality Aspects of Mobile Banking - Public and Private Sector Banks in India - M. N. Koti; P. Verma; N. Singh (Финансы: теория и практика)
In response to the increased global competition within the banking industry, financial institutions are diligently exploring the deployment of new banking technologies to improve both the quality of their banking infrastructure and customer. The purpose of this study is to assess the quality aspects (information quality and service quality) of mobile banking on perceived satisfaction and word of mouth and the variation in the proposed relationship between public and private sector banks in India. The research methodology: for data collection, a survey was conducted on 230 mobile banking users by using a random sampling technique. For analysis we used partial least square structural equation modelling with the help of Smart PLS 4.0. The result depicts that perceived satisfaction is significantly impacted by service quality, and also the impact of perceived satisfaction on word of mouth is positively significant, which indicates the importance of quality parameters during the use of m-banking. Meanwhile information quality was found to have an insignificant effect on perceived satisfaction. The variation demonstrates that the impact of service quality on perceived satisfaction was stronger in the public sector banks than in the private sector banks. The findings of the study will help in improving retention rate of m-banking consumers and determining consumer preference in different sectors of banks.